Development of an ISO9001:2000 Self-Assessment Tool for Use in ISO-Certified Manufacturing Companies - Tayefeh Morsal, Seyed Ali Asghar (2008)
Measuring and computing the maturity of the Quality Management System (QMS) is one of the most important requirements in ISO 9001:2000. Many organizations have not found any accurate and unique approach to QMS maturity assessment. Considering this fact, the ISO has never issued any self assessment model. However, some ISO certified organizations have to apply the award models. Some of certified organizations have even become compelled to change one of the award models according to their needs. Nevertheless, in applying it, this approach has caused many difficulties for them. The main objective of this research was developing a proper self-assessment tool in accordance with the ISO9001:2000 requirements. The process of developing a self-assessment tool was carried out in three stages. In the first stage, the framework of the tool was developed, while it was compiled according to the ISO requirements in the second stage. This tool was formed by eight principles, 33 criterions and 300 indicators. Each principle was organized into many criteria and indicators, which provided necessary situation for judgment. Audit team investigated the effectiveness, efficiency and suitability of their QMS using the present tool. The third stage allocated tool verification and validation. Verification was performed by comparing the requirements of ISO and the content of the tool and expert’s views. Meanwhile the validation was carried out by pilot test and case study. A certification body and two consulting services companies studied the tool and offered their opinions; whereas, eight volunteered ISO certified manufacturing companies applied the tool to assess and test it in the real environment. The data obtained from the case studies and the investigations by the experts were analyzed. The results showed that, the developed self-assessment tool could be used to investigate the QMS maturity of the organizations.